2021
DOI: 10.3390/ma14061464
|View full text |Cite
|
Sign up to set email alerts
|

Clindamycin-Based 3D-Printed and Electrospun Coatings for Treatment of Implant-Related Infections

Abstract: This study presents the development and characterisation of two novel bioactive coatings deposited on TiAlV and AISI 316LVM substrates. The coatings were prepared using 3D printing and electrospinning. The 3D-printed coating consisted of the cellulose nanofibril suspension, alginate, and carboxymethylcellulose (CMC), while CMC and polyethylene oxide were used to prepare the electrospun coating. Both coatings were loaded with the antibiotic clindamycin (CLIN), which is a bacteriostatic lincosamide known for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Using ATR-FTIR, the bioactivity of prepared coatings was confirmed by signals related to PO 4 3 − , indicating apatite, in a study by De Santis et al [ 69 ] after ceria was combined with TNTs and soaked in SBF at 37 °C for 8 days. The technique can also offer information on whether the drug was successfully incorporated into the bioactive coatings and whether it was physically or chemically bound to the coatings [ 32 , 34 , 85 , 86 , 87 , 88 , 89 , 90 ]. In a study by Kiran et al [ 87 ], coatings of poly(ε-caprolactone) (PCL) nanofibers loaded with HA and rifampicin were electrospun on a Ti substrate.…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using ATR-FTIR, the bioactivity of prepared coatings was confirmed by signals related to PO 4 3 − , indicating apatite, in a study by De Santis et al [ 69 ] after ceria was combined with TNTs and soaked in SBF at 37 °C for 8 days. The technique can also offer information on whether the drug was successfully incorporated into the bioactive coatings and whether it was physically or chemically bound to the coatings [ 32 , 34 , 85 , 86 , 87 , 88 , 89 , 90 ]. In a study by Kiran et al [ 87 ], coatings of poly(ε-caprolactone) (PCL) nanofibers loaded with HA and rifampicin were electrospun on a Ti substrate.…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
“…Therefore, it can be concluded that the hydrophilicity of implant surfaces can be improved by applying certain types of coatings. The hydrophilicity of metal-based implants has been improved by the application of TNT/nTiO 2 [ 85 ], HA [ 190 ], BG [ 191 ], and various polymers [ 32 , 87 , 192 ]. Nevertheless, although contact angle measurements can provide information on the interactions between the surface and gases or liquids, other techniques should be employed to provide more detailed characterization of chemical properties, as described in the sections above [ 178 ].…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface morphology and porosity of all final 3D printed scaffolds were analyzed by scanning electron microscopy (SEM) [37]. Before imaging, all freshly 3D printed scaffolds were frozen at −80 • C, lyophilized, and pressed on a double-sided adhesive carbon tape (SPI Supplies, West Chester, PA, USA).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Further research is needed to determine whether replacing amoxicillin with clindamycin may improve implant prognosis. Recent research suggests that a new technology, 3D-printed CLIN, allows the stratification of titanium orthopedic implants in a compound that allows the long-term release of clindamycin to prevent postoperative infections [70]. This technology has all the prerequisites to be successfully introduced in oral implants, minimizing the risk of post-operative bacterial contamination and reducing failure rates.…”
Section: Clindamycin and Implant Therapymentioning
confidence: 99%